Ambiguous Facilitation: An Ethnographic Study of the Contextual Aspects of Participation in Group Activities in a Norwegian Healthy Life Centre - Tonje Cecilie Indrøy; Lisbeth Kvam; Aud Elisabeth Witsø (Societies, 2023)
Background: Participation is essential in health promotion initiatives such as the Norwegian Healthy Life Centres (HLCs) which offer lifestyle-related guidance to people with lifestyle-related diseases or at risk for such diseases. While participation has been studied in this setting from the perspectives of health personnel or service users, no studies have been conducted on the contextual aspects of participation through studying the interactions between the actors involved in group activities within the service. To lead group activities requires competency in facilitation of learning in groups. The aim of this study is to explore participation in group activities in the context of a Norwegian HLC by studying the interaction between the various actors involved in the activities there. Methods: An ethnographic study was designed based on participant observation of physical activity groups and a healthy nutrition group in a Norwegian HLC over a period of three months. Findings: The findings suggest that (1) the multiple roles of the Health Professional (HP), (2) the process of goal setting, and (3) time frames and the physical context are central contextual aspects of participation in this setting, leading to an ambiguous facilitation of group activities.